Pencatatan Keuangan Sederhana sebagai Sarana Optimalisasi Pengelolaan UMKM di Wilayah Ranting Nasyiatul Aisyiyah Talagening: Simple Financial Recording as a Means of Otimizing MSME Management in the Nasyiatul Aisyiah Talagening Branch Area - Winarni, Dwi; Arofah, Rifka Utami; Pratama, Havidz Cahya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Micro, small, and medium enterprises (MSMEs) are one of the business groups that have a major role and contribution to the economy in Indonesia. MSMEs also have advantages in terms of resilience to economic instability. Thus strengthening the MSME group is urgently needed so that it can continue to grow and be able to face global competition. Participants are MSME actors who are in the Nasyiatul Aisyiyah Talagening Branch, Bobotsari District, Purbalingga Regency. Based on the survey results, the problems encountered include the absence of structured financial records due to difficulties, a lack of understanding of accounting, and a lack of understanding of the benefits of recording business finances. A series of training and assistance on simple bookkeeping, among others by socializing the importance of simple bookkeeping, training on recording expenses and reporting, as well as analyzing the results of financial records that have been made. The method used is training with a participatory rural appraisal (PRA) approach to involve participants in identifying problems, implementing solutions, and monitoring evaluations. So that they can contribute knowledge and practice of simple bookkeeping or simple financial records with their respective business and financial conditions.